Evaluation of soil structural quality and soil fertility indicators of dryland and fadama milieus based on soil profile description at 0–20 cm soil depth - Suleiman Usman; James O. Jayeoba (Discover Soil)
Abstract Soil profile pits from 0 to 20 cm soil depth for eighteen (18) different soil pedons in the dryland and fadama areas of Kebbi State, Nigeria, were used to evaluate the soil structural quality and soil fertility indicators for soil management suggestions. Soil structural quality was assessed and classified according to the general guidelines for in USDA-NRCS whereas soil fertility status was evaluated based on the soil data obtained from laboratory analysis. There was link between the dryland and fadama sites for %OC, %OM and %N but differ slightly for pH, Ca, Mg, K, Na, NPK ratios and soil reaction (pH). Nitrogen and phosphorus were low but potassium appeared to be moderate. The common ratios for NPK compounds in the fadama site were 1:1:2, 1:1:3, 1:1:4 and 1:2:5; however, in the dryland site, there were diverse ratios, which appeared to differ from one site to another. Three (3) classes of CEC were recorded for dryland namely very-low, low, and moderate. Likewise there were other three (3) classes for fadama (low, moderate, and high). Soil pedons 1, 2, 5, 7, and 8 were extremely acidic, while soil pedons 10 and 18 were strongly acidic. Similarly, soil pedons 9, 12, 15, and 17 were moderately acidic whereas soil pedons 3, 4, 11, 13, and 14 were slightly acidic, and soil pedons 6 and 16 were observed neutral and slightly alkaline, respectively. The soil structural quality was evaluated as weak, very weak, moderate, strong, and good structures. In fadama, the sites were evaluated as well and good structures. The study suggested that the dryland and fadama sites can be managed under the following conservation approaches: (a) the regular use of organic manure, (b) application of chemical fertilizer, and (c) the use of organic residues (plant and animal materials).